Low-complexity DOA estimation method for a co-prime linear array - Wu, Xuchen; Yang, Xiaopeng; Han, Bowen; Xu, Feng (Journal of engineering (Stevenage, England), 2019)
The problem of direction-of-arrival (DOA) estimation for a co-prime linear array is researched. A low-complexity DOA estimation method is proposed. The co-prime array is decomposed into two sparse uniform linear sub-arrays whose inter-element spacing meets the co-prime condition. Then the received signals of the two sub-arrays are processed for statistical signal processing. Although the DOA estimation based on the under-sampled signal will produce phase ambiguity, the sparse array element spacing that satisfies the co-prime condition makes the phase ambiguity have certain periodic rules. Finally, the unique solution corresponding to the true DOA can be obtained in the phase ambiguities of the two sub-arrays through the application of the co-prime nature. Simulation results validate the effectiveness of the proposed method.